Simulated transactions from a common-law perspective and whether this doctrine is still relevant in respect to the application of the current anti-avoidance rules - Fredericks, Martin (Department of Finance and Tax, 2017)
The purpose of this paper is to analyse the common-law principles pertaining to simulated transactions in an effort to protect our tax base and to expose unlawful tax evasion. This paper highlights what is currently regarded as a 'simulation' and how South Africa compares to international practices. I have divided my discussion into five parts, viz: 1. Analysis of the requirements for an effective tax system; 2. Discussion of common-law principles; 3. Simulated transactions from a common law perspective, 4. International case law on simulated transactions; and 5. Relevance of common-law principles to the current GAAR.